Production of kombucha from citrus leaf waste to improve economy and health in Cigugurgirang KBB - Nunung Kurniasih; Tina Dewi Rosahdi; Lia Kamelia; Liberty Chaidir (University of Merdeka Malang, 2026)
Cigugurgirang Village, located in Parongpong District, West Bandung Regency, has abundant citrus farming potential. However, the utilization of citrus leaf waste as a commodity with economic and health value remains very limited. In fact, citrus leaves contain bioactive compounds that have the potential to be used as raw materials for functional beverages such as kombucha. Kombucha, in addition to having high nutritional value, is also a fermented drink with strong market potential. This community service program aims to improve public health and economic independence by transforming citrus leaf waste into a functional kombucha product through the active participation of local farmer groups. The method used is a Participatory Action Research (PAR) approach combined with the Asset-Based Community Development (ABCD) approach, involving citrus farmer groups as the main partners. Data were collected through field observations, interviews, and Focus Group Discussions (FGD). The results showed that kombucha fermented for 8 days had the highest nutritional value and was most preferred in terms of taste, aroma, and color. Through a participatory assistance process and the utilization of local assets, the community is able to produce a functional kombucha beverage that not only supports health but also creates new environmentally friendly economic opportunities.